Pengaruh Kualitas Laporan Keuangan, Sistem Pengendalian Internal, Dan Aksesibilitas Laporan Keuangan Terhadap Akuntabilitas Pengelolaan Keuangan Daerah (Studi Kasus Pada Badan Keuangan Dan Aset Daerah Kabupaten Bandung Barat Tahun 2021) - Fernanda Alivia Defana; Sri Rahayu (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
This study aims to determine the effect of Quality of Financial Reports, Internal Control Systems, and Accessibility of Financial Reports on Regional Financial Management Accountability both simultaneously and partially. This research is included in the verification descriptive research. The population in this study were all BKAD employees of West Bandung Regency in the BMD Management and Accounting fields. Sampling technique in this study used non-probability sampling through saturated sampling, where all members of the population were used as samples, obtained as many as 50 employees. The data analysis model used in this study is multiple linear regression analysis using software version 25. The results show that the quality of financial reports, internal control systems, and accessibility of financial reports simultaneously affect the accountability of regional financial management. Based on the partial test results, the internal control system has no effect on the accountability of regional financial management, while the quality of financial reports and the accessibility of financial reports have a significant effect on the accountability of regional financial management.